2015
DOI: 10.4049/jimmunol.1401492
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Inhibits T Cell Adhesion by Recruiting CAPRI to the Plasma Membrane

Abstract: CD28 is a coreceptor expressed on T lymphocytes. Signaling downstream of CD28 promotes multiple T cell functions such as proliferation, survival, and cytokine secretion. Adhesion to APCs is another function of T cells; however, little is known with regard to the role of CD28 in this process. Our previous studies have shown that CD28 inhibits T cell adhesion, but the underlying mechanism that mediates this process remains unknown. In the present study we discovered that signaling downstream of CD28 resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Both on B7.2 + anti-CD3 and B7.2•anti-CD3, the cells spread less as compared to all other cases reported. This may be related to previous reports which showed that CD28 inhibits cell spreading by acting on LFA-1 related down-stream signaling ( 55 ). Here, a similar effect seems to be operational even though LFA-1 ligands are not present.…”
Section: Discussionsupporting
confidence: 86%
“…Both on B7.2 + anti-CD3 and B7.2•anti-CD3, the cells spread less as compared to all other cases reported. This may be related to previous reports which showed that CD28 inhibits cell spreading by acting on LFA-1 related down-stream signaling ( 55 ). Here, a similar effect seems to be operational even though LFA-1 ligands are not present.…”
Section: Discussionsupporting
confidence: 86%
“…This different dependence on TSP-1 is logical, since TSP-1 is proadhesive ( 19 , 21 ), and CD28 ligation should not be allowed to induce adhesion and arrest of naïve T cells searching for their cognate antigen. This assumption is supported by results showing that CD28 ligation antagonizes adhesive contacts ( 44 ).…”
Section: Co-stimulation Through Inhibition Of Lrp1-targeted Immunosupmentioning
confidence: 56%
“…RASA4 is a fetal-biased primate-specific gene that was also one of the top downregulated genes in Non-TD subjects. RASA4 is a GTPase-activating protein in the Ras signaling pathway that functions in the activation of T cells, mast cells, and macrophages [7779]. Children with Non-TD were also observed to have downregulation of GNAO1 , encoding a G protein alpha subunit important for neurodevelopment and synaptic signaling.…”
Section: Discussionmentioning
confidence: 99%